Exploring payment behavior for live courses in social Q&A communities: An information foraging perspective. Issue 4 (July 2020) - Shi, Xiao; Zheng, Xiabing; Yang, Feng
Highlights: Social endorsement strongly negatively moderates the relationship between willingness to pay and payment behavior. Perceived quality of free content, perceived credibility of content creators, and perceived quantity of participants positively influence users' willingness to pay. Perceived likeability of content creators has no significant influence on users' willingness to pay. The relationship between perceived likeability of content creators and willingness to pay could be mediated by perceived credibility of content creators. Abstract: People are increasingly searching for information in social Q&A communities, especially through a new form of paid knowledge product, namely, live course. Such course provides a way for users to interact synchronously with content creators online. However, how this knowledge product is accepted and why users pay for it deserve attention from researchers. In this study, a research model was developed based on information foraging theory (IFT) and social information foraging (SIF) theory to analyze users' information processing and evaluation when making payment decisions. Our research model was validated by collecting subjective and objective data from a Chinese social Q&A community that has been successful in offering live course services. We found that perceived quality of free content, perceived credibility of content creators, and perceived quantity of participants positively influence users' willingness to pay, and thus, positively affects users' payment behavior. Unexpectedly, social endorsement negatively moderates the relationship between willingness to pay and payment behavior. This study enhances the theoretical understanding of the drivers of users' payment for live courses in social Q&A communities. For IS practice, our findings provide unique insights for community managers and content creators on how to operate paid knowledge products appropriately and effectively.